2020
DOI: 10.1007/s12144-020-01178-1
|View full text |Cite
|
Sign up to set email alerts
|

How to become more grateful? The mediating role of resilience between empathy and gratitude

Abstract: The current study examined the relationship between empathy, resilience, and gratitude. Specifically, the study investigated the potential mediating role of resilience between empathy and gratitude. The study involved 214 participants who completed the Gratitude Resentment and Appreciation Test-Revised (GRAT-R), the Questionnaire of Cognitive and Affective Empathy (QCAE), and the Resilience Measurement Scale (SPP-25). The results showed significant positive correlations among resilience, empathy, and gratitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 56 publications
1
8
0
1
Order By: Relevance
“…We found that perspective-taking could positively predict prosocial behaviors of college students in China, which is consistent with previous research ( Ding and Song, 2017 ; Chen et al, 2020 ; Lasota et al, 2020 ). A possible reason for this outcome is that perspective-taking enables an individual to make flexible reappraisals of social situations, facilitating more harmonious social interactions and prosocial behavior ( Wolgast et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that perspective-taking could positively predict prosocial behaviors of college students in China, which is consistent with previous research ( Ding and Song, 2017 ; Chen et al, 2020 ; Lasota et al, 2020 ). A possible reason for this outcome is that perspective-taking enables an individual to make flexible reappraisals of social situations, facilitating more harmonious social interactions and prosocial behavior ( Wolgast et al, 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, the Broaden-and-Build theory of positive emotions suggests that gratitude is a positive emotion that can increase individuals’ mental flexibility, help construct psychological resources, and motivate prosocial behavior ( Fredrickson, 2001 , 2004 ). When individuals are in a positive emotional state, they will have a stronger prosocial motivation that inspires their prosocial behavior ( Chen et al, 2020 ; Lasota et al, 2020 ; Yang et al, 2021 ). Nevertheless, no studies have examined gratitude as a potential mechanism that underlies the associations among different types of empathy and prosocial behaviors among Chinese college students.…”
Section: Introductionmentioning
confidence: 99%
“…A series of recent observational studies directly examined the relationships between empathy and other components of emotional and personality domains: e.g., emotional intelligence [24,25], emotional regulation [26,27], and resilience [27]. Interestingly, empathy is frequently viewed as a component of emotional intelligence, and if the latter is viewed as a non-cognitive ability, so is the former [28].…”
Section: Empathymentioning
confidence: 99%
“…From education, the result of a peace education program revealed that Jewish and Arab female high school students were more dovish than the males to use peaceful and diplomatic methods to gain their achievements or face conflicts [28]. And consisted with past studies, most females reported positive attitudes and gratitude than males [29]. For having greater empathized ability which has been found its ways for having impacts into mainstream practices (e.g., customer service; [30]), it is female's gift to understand and have heartresonances with others' experience and feelings not only narrowed in reality but towards emotions literary works want to express by words for having functions and abilities to invoke people's imaginations (e.g., sympathy).…”
Section: Approved Reasons Of Hypotheses 1and2mentioning
confidence: 99%